1945. Effects of COVID-19 Vaccines on Outcomes Among Hospitalized COVID-19 Patients. (15th December 2022) - Hoskins, Serene; Restrepo, Marcos I; Cadena, Jose
Abstract: Background: After COVID-19 vaccinations, breakthrough infections appear to be of public health concern. There is limited data regarding clinical effectiveness of COVID-19 vaccination. Our aim was to determine the differences in clinical outcomes among COVID-19 unvaccinated versus vaccinated patients who required hospitalization. Methods: This was a retrospective cohort study of COVID-19 hospitalized patients between 7/25/21 and 9/6/2021. Previously infected COVID-19 patients were excluded. The patients were classified as fully vaccinated vs. unvaccinated (CDC guidelines). The primary outcome included the need for advance oxygen therapy (high flow nasal cannula, non-invasive ventilation, mechanical ventilation), ICU admission, or 28-day all-cause mortality. We performed a subgroup analysis according to the immunocompetent status and older age (≥65 years). Results: We enrolled 207 patients, stratified as unvaccinated (n=147 [71%]) vs. fully vaccinated (n=60 [29%]). Unvaccinated patients were younger (median age 58 vs. 71 years old, p< 0.001) and more likely to require oxygen (n=105[71%] vs. n=35[58%], p=0.07) compared to vaccinated patients. Unvaccinated patients were more likely to reach the primary outcome (n=59 [40%] vs. n=16 [26%], p=0.08) when compared to vaccinated patients. The subgroup analyses revealed that unvaccinated patients had higher rates of the primary outcome when ≥65 years old ( n=27/46 [58.7%] vs. n=13/37 [35.1%], p=0.047), immunocompetent (n=57/139 [41%] vs. 13/53 [24.5%]) and both groups combined (n=22/39 [56%] vs. 11/38 [28.9%], p=0.021), respectively. Conclusion: Unvaccinated patients represented the largest proportion of hospitalized patients. Unvaccinated patients were younger and required oxygen therapy. Unvaccinated immunocompetent patients aged ≥ 65 had worse outcomes compared to vaccinated patients. Further studies are needed to identify unmeasured characteristics that may be associated with poor clinical outcomes. Disclosures: All Authors : No reported disclosures.